Screening of rice (Oryza sativa) germplasm for resistance to brown spot caused by Cochliobolus miyabeanus - KUMAR, SANJEEV; KUMAR, RAKESH; AZAD, CHANDRA SHEKHAR; SINGH, SARDAR SUNIL (The Indian Journal of Agricultural Sciences, 2025)
Brown spot of rice, caused by Cochliobolus miyabeanus, remains one of the most destructive diseases affecting rice productivity, particularly under the natural epiphytotic conditions of eastern India. The use of resistant cultivars is the most economical, practical, and environmental safe strategy for managing the disease. The study was carried out during the rainy (kharif) seasons of 2021 and 2022 at Bihar Agricultural University, Sabour, Bihar to evaluate 267 rice (Oryza sativa L.) genotypes against brown spot under natural disease pressure. Disease severity was assessed following the IRRI Standard Disease Rating Scale (2002). The results revealed considerable variation among genotypes for disease response. Only five entries IET 19512 (US 311), IET 18667 (OR 2089-9), IET 18668 (OR 2060-9), IET 20007 (RPHR 205-14-3-2), and HPR 2529 exhibited high resistance. Additionally, 17 genotypes were categorised as resistant and 20 genotypes as moderately resistant, while the remaining entries were susceptible or highly susceptible. The findings highlight valuable resistant sources that can be utilised in breeding programmes aimed at developing brown spot-resistant rice cultivars suitable for the Indo-Gangetic Plains of eastern India.